Dinamika Mortalitas Penduduk di Kota Medan dan Implikasinya terhadap Kebijakan Kesehatan Perkotaan - Abdullah Rasyid (CV. ALIM'SPUBLISHING, 2026)
Medan City, as a center of metropolitan growth, has achieved a very high Human Development Index (HDI). However, it still presents a paradox in the form of sharp mortality disparities across social groups and administrative areas, making Medan City an important case for study. This study employs a qualitative approach using policy analysis based on Walt & Gibson policy implementation model. Secondary data were collected through documentation studies of official reports from Statistics Indonesia (BPS) and the Health Office, policy documents, and sectoral statistics related to mortality. The findings indicate that, in general, mortality rates in Medan City have declined over the medium to long term, as reflected in the decrease in infant, under-five, and maternal mortality rates, along with an increase in life expectancy. However, this decline has not been evenly distributed, as disparities remain across administrative areas and socioeconomic groups. Medan City also faces the challenge of a double burden of disease, marked by the dominance of non-communicable diseases alongside the continued presence of communicable diseases among certain population groups. The effectiveness of mortality reduction policies is influenced by communication, resources, implementer disposition, and bureaucratic structure. Therefore, a policy model is needed that emphasizes equitable resource distribution, the strengthening of primary healthcare services, and integrated cross-sectoral preventive and promotive approaches. This study recommends strengthening policy implementation, improving the capacity of policy implementers, and integrating health policy with other sectors to achieve inclusive and sustainable mortality reduction.